Where did the river go? - Corey, Peter (Learndirect skill and qualifactions London, 2007)
Content : As shown in pictures ,you can find measurement of the book under product dimensions , Book type and age recommendation is mentioned below . this is a preloved book and we have checked for wear and tear , we dont take any returns on preloved books since we sell at very affordable costs . Kindly take unboxing video of any order you place with us .